2000
DOI: 10.1007/bf02495173
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of triple-decker iron and cobalt complexes with a central tetramethylphospholyl ligand

Abstract: ul. Vavilova, I 17813 Moscow, Russian Federation. Fax: +7 (095)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Complexes 1, [24] 2, [25] 3, [8] 4, [26] 5, [1] 6, [27] 7 [1] and 8, [27] were prepared as described in the literature. All of the compounds examined in this study were rapidly transferred from sealed ampoules to screw-cap perspex sample holders, sealed with Teflon tape and rapidly cooled to 78 K. Mössbauer spectra were recorded at increasing temperatures (in 20 K steps) to the maximum temperature, and then in a cooling mode to ascertain the reversibility of the data.…”
Section: Methodsmentioning
confidence: 99%
“…Complexes 1, [24] 2, [25] 3, [8] 4, [26] 5, [1] 6, [27] 7 [1] and 8, [27] were prepared as described in the literature. All of the compounds examined in this study were rapidly transferred from sealed ampoules to screw-cap perspex sample holders, sealed with Teflon tape and rapidly cooled to 78 K. Mössbauer spectra were recorded at increasing temperatures (in 20 K steps) to the maximum temperature, and then in a cooling mode to ascertain the reversibility of the data.…”
Section: Methodsmentioning
confidence: 99%
“…1- 6 We have recently de scribed the efficient methods for the syntheses of the co balt tetramethylcyclobutadiene complexes with five elec tron ligands of different types. [7][8][9][10][11][12][13] In this work, we syn thesized the [Cb*CoL] + complexes (Cb* = C 4 Me 4 , L is polyarene).…”
mentioning
confidence: 99%
“…They are best prepared by the method described above, but have also been prepared from g 3 -cyclobutenonylcobalt complexes [29]. In the intervening years many isometallocenes, incorporating a wide range of metal centres, have been described [29][30][31][32]. In 1987, Pauson et al reported a series of (tetramethylcyclobutadiene)isocobaltocenium salts of the general formula [(g 4 -C 4 Me 4 )Co(g 6 -arene)] + [33].…”
Section: Syntheses Of the Isocobaltocenium Salts (2-4)mentioning
confidence: 97%
“…In 1987, Pauson et al reported a series of (tetramethylcyclobutadiene)isocobaltocenium salts of the general formula [(g 4 -C 4 Me 4 )Co(g 6 -arene)] + [33]. These were prepared by refluxing [(g 4 -C 4 Me 4 )Co(CO) 2 in stacking reactions [32], and other ligand displacement processes [10].…”
Section: Syntheses Of the Isocobaltocenium Salts (2-4)mentioning
confidence: 98%